Corporate taxation and investment in South Africa - Maboshe, Mashekwa (School of Economics, 2022)
This thesis investigates some aspects of corporate taxation and firm-level investment in South Africa. The thesis uses specially constructed and unique datasets to draw insights on the link between corporate tax changes and firm-level investment and as well as the efficiency of capital allocation in South Africa. The thesis comprises a short introductory chapter, three empirical chapters, and a summary chapter. The first empirical chapter (chapter 2) evaluates the responsiveness of firm-level investment to corporate tax changes over a period of notable corporate tax reforms in South Africa. The study estimates a reduced form neoclassical investment model using a particularly constructed dataset of firms listed on the Johannesburg stock exchange over the period 1999-2012. Generalised methods of moments (GMM) techniques are used to control for various econometric biases. The findings suggest that although the corporate tax reforms reduced the marginal cost of investment, these reductions did not result in a statistically significant increase in firm-level investment. The null effects found in this study are robust to various estimation specifications. Although at variance with the established literature from developed countries, the findings are similar to emerging evidence in other developing country contexts and suggest that other factors may be more important determinants of investment than corporate tax policy. Chapter 3 explores the possibility that the unresponsiveness of firm-level investment to corporate tax policy may be a result of the presence of financial constraints. According to the financial constraints hypothesis, neoclassical fundamentals may fail to explain investment in the presence of financial constraints. The paper investigates the role of financial constraints in investment using dynamic GMM and endogenous switching regressions methods. The paper finds that financial constraints are an important factor in investment determination. Firms that are more financially constrained rely more on the availability of internal resources to fund investment relative to the less financially constrained firms. The findings suggest that investment policy should consider strategies that reduce informational asymmetries and other capital market inefficiencies. Such strategies would help lower the barriers and costs of external finance, thus improving firm-level investment. Chapter 4 considers the implications of differential taxation of assets and industries in South Africa. The paper's motivation is that although there are variations in the tax treatment of investments in assets and across industries, little empirical evidence exists on the nature of any investment distortions due to differential tax policies. Using a rare and unexplored industrylevel data source from Statistics South Africa, the study constructs a panel of asset shares by industry over the period 2007-2014 and estimates inter-asset tax elasticities to estimate the potential investment distortion or misallocation effects of differential taxation policies. The findings suggest the presence of non-negligible inter-asset distortions due to non-uniform taxation of investments. Investments in a given asset are found to respond to the tax incentives provided for other asset classes. Our findings suggest that current corporate tax policies that offer differentiated and asset or industry-specific investment incentives may be causing distortions and inefficiencies in the allocation of assets among industries.